Growth and pubertal development in elite female rhythmic gymnasts - Georgopoulos, N.; Markou, K.; Theodoropoulou, A.; Paraskevopoulou, P.; Varaki, L.; Kazantzi, Z.; Leglise, M.; Vagenakis, A. G. (The Journal of Clinical Endocrinology & Metabolism, 1999)
Optimal growth depends upon both environmental and genetic factors. Among environmental factors that could alter growth and sexual maturation are stress and intensive physical training. The influence of these factors has been documented in a variety of sports, but there is limited information on rhythmic gymnasts, who have entirely different training and performance requirements. The study was conducted during the 13th European Championships in Patras, Greece, and included 255 female rhythmic gymnasts, aged 11-23 yr. The study included measurement of height and weight, assessment of breast and pubic hair development, estimation of body fat and skeletal maturation, and registration of menarcheal age and parental height. Gymnasts were taller than average height for age, with mean height above and mean weight below the 50th percentile. Actual height SD score was positively correlated to weight SD score (P < 0.001), number of competitions (P = 0.01), and body mass index (BMI; P < 0.001). Predicted adult height SD score was positively correlated to weight SD score (P < 0.001) and negatively to body fat (P = 0.004). There was a delay in skeletal maturation of 1.3 yr (P < 0.001). Pubertal development was following bone age rather than chronological age. The mean age of menarche was significantly delayed from that of their mothers and sisters (P = 0.008 and P = 0.05, respectively), was positively correlated to the intensity of training and to the difference between chronological age and bone age (P < 0.001 and P = 0.002, respectively), and was negatively correlated to body fat (P < 0.001). In the elite female rhythmic gymnasts, psychological and somatic efforts have profound effects on growth and sexual development. Despite these aberrations, adult height is not expected to be affected.